Orientilist Bernard Louis's Approach, in Studing the Concept of Revolution in Islam - Zahida Taha (My University, 2015)
Bernard Lewis, is one of the most prominent figures in the Western world Orientalist, and his fame came through the supply of the Western world with the needed academic studies related to Islam and Muslims, which contributed to the political decision-making, whether in Britain or the United States of America. The study of Lewis on the subject of revolution in Islam was one of the most prominent topics that reflect the reality of the relationship between Orientalism and politics, which cared for Lewis out through his research on the concept of revolution in Islam, and compared the Western sense of revolutions, starting point of the idea that the relationship between religion and the state in the Islamic East himin the Christian West. Lewis sought in his studies about subject (revolution) to warn the Islamic countries of the risk of falling under the influence of factors of the development of the West and the introduction of its cultural system, because the culture of the West and political concepts will not only serve to increase the problems of Muslims. Lewis tried to alert the west of the danger of going too far in attempts that seek to separate religion from politics in the Islamic world, because such attempts are only temporary and superficial. And not only the type of deviation is natural, and that these attempts nearing completion in Islamic countries that try to apply such a new ideology on the ruling system, as is the case with Iran and Turkey. Lewis tried to prove his theory by searching historical linguistic connotations of the term revolution, and follow developments of this term in the political work of the contemporary Islamic movements; compared the experiences of contemporary governments. Although the views of Bernard Lewis in this area was characterized by capacitive and accuracy; but he could not get rid of the influence of Western cultural, political affiliation, and ideological. The salient feature of the results of Lewis in that area public judgments; especially in the analysis of the contemporary revolutions reasons and motives of social, political and religious.

يعد المستشرق برنارد لويس من أبرز الشخصيات الاستشراقية في العالم الغربي، وجاءت شهرته من خلال إمداد العالم الغربي بما يحتاج إليه من دراسات اكاديمية تخص الإسلام والمسلمين، وتسهم في صناعة القرار السياسي. كانت دراسة لويس لموضوع الثورة في الإسلام أحد ابرز الموضوعات التي تُظهر واقع العلاقة بين الاستشراق والسياسة، والذي اهتم به لويس من خلال مقارنته بالمفهوم الغربي للمصطلح، منطلقا من فكرة اختلاف العلاقة بين الدين والدولة في الشرق الإسلامي عنه في الغرب المسيحي. حاول لويس إثبات نظريته من خلال البحث اللغوي التاريخي لمصطلح الثورة، وتتبع تطورات هذه المصطلح في أدبيات الحركات الإسلامية المعاصرة. وعلى الرغم من أن آراء برنارد لويس في هذا المجال إمتازت بالسعة؛ لكنه لم يستطع التخلص من تأثير الثقافة الغربية، والانتماء السياسي، والعقائدي. فكان من أبرز سمات آراء لويس في هذا المجال: إصدار الأحكام العامة؛ خصوصا في تحليل أسباب الثورات المعاصرة ودوافعها الاجتماعية، السياسية والدينية. سعى لويس في دراساته لموضوع (الثورة) إلى تحذير الدول الإسلامية من مغبة الوقوع تحت تأثير الغرب والأخذ بنسقه الحضاري، لأن ثقافة الغرب ومفاهيمه السياسية لن تعمل إلا على زيادة مشاكل المسلمين. وحاول تنبيه التيارات الغربية في العصر الحديث من مغبة التمادي في المحاولات التي تسعى إلى فصل الدين عن السياسة في العالم الإسلامي، لان تلك المحاولات ما هي إلا وقتية وشكلية، ولا تعدو أن تكون سوى انحراف، وان هذه المحاولات أوشكت على الانتهاء في الأقطار الإسلامية التي حاولت تطبيق مثل هذه الإيديولوجية الجديدة على نظام حكمها؛ إلا أنها لم تنجح في ذلك، كما هو الحال مع إيران وتركيا. ولا يعدو مصطلح (ثورة) في العالم الإسلامي من وجهة نظر لويس إلا إسقاط خاطئ لمفهومِ المصطلح الغربي على الثورات في العالم الإسلامي؛ ضد أنظمة تراها تلك الحركات خارجة عن الشريعة الإسلامية، ولا تحمل أبعاد الثورات التي حدثت في الغرب؛ فالثورة في المفهوم الإسلامي غير الثورة بوصفه مصطلحا غربيا.
منهج المستشرق برنارد لويس في دراسة مفهوم الثورة في الاسلام